ANALYSIS OF THE USE OF MENSTRUAL PAD, TAMPONS, AND MENSTRUAL CUP DURING MENARCHE - Dewi Luberty Warashinta; Asti Melani Astari; Ayut Merdikawati (Journal of Community Health and Preventive Medicine, 2021)
Various kinds of alternative product innovations have been to substitute disposable sanitary napkins for reducing the increasing waste of disposable sanitary napkins and reduce environmental pollution. The products in question include, among others, menstrual cups, tampons. Tampons and menstrual cups are still rarely used by Indonesian women because there is little knowledge about menstrual hygiene and how to use them are still considered taboo. The objective of the study is to compare the analysis of the use of sanitary napkins, tampons, and menstrual cups during menarche. The method used in this study is a literature study from the journal published in 2015-2020. The database was from Ebsco, ProQuest, and Science Direct database, and 231 articles were obtained and filtered so that the final result were 12 articles that matched. The results of the comparison of the use of sanitary napkins, tampons, and menstrual cups in terms of hygiene and safety, environmental impact, and effectiveness showed that menstrual cups were superior to the other two products. In conclusion, the alternatives menstrual sanitation tools besides sanitary napkins are tampons and menstrual cups. This paper can be the basis for further research using different research designs to obtain more complete data.